PENGARUH IMPLEMENTASI SISTEM PENGENDALIAN MANAJEMEN DAN AUDIT OPERASIONAL TERHADAP PENILAIAN KINERJA KARYAWAN (SURVEI PADA PT TRISCO TAILORED APPAREL MANUFACTURING) - Sinta Noviyanti (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2018)
The purpose of this study is to find out how much Implementation of Management Control Systems on Employee Performance Appraisal and also to know how effective Operational Audit on Employee Performance Appraisal. The object of this research is Garment company in Bandung. Variables used in this study are Employee Performance Appraisal as a dependent variable, Implementation of Management Control Systems and Operational Audit as independent variables The results showed Implementation of Management Control System 7.01 % on Employee Performance Appraisal and Operational Audit 52.1% on Employee Performance Appraisal.